2021
DOI: 10.31234/osf.io/2umfe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

There are Higher Levels of Conspiracy Beliefs in More Corrupt Countries

Abstract: In three studies, I found evidence that people living in less socially inclusive countries (operationalized as having weaker rule of law, and lack of equality and press freedom) have a greater tendency for conspiracy ideation. In Study 1 (21 countries, N = 22,238), participants in less inclusive countries were more likely to believe in conspiracies, even after adjusting for country-level differences in educational performance. Study 2 (24 countries, N = 4,743) and Study 3 (23 countries, N = 5,726) replicated t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 28 publications
5
29
0
Order By: Relevance
“…There is further evidence that conspiracy beliefs might be more reasonable in contexts with high risk of being under threat. In a recent study, it was found that the negative correlation between education and conspiracy beliefs is weaker in high corruption countries, as compared to low corruption ones (Alper, 2021). One potential explanation is that being suspicious of potential conspiracies is relatively more reasonable in high corruption contexts, and thus even highly educated people find them more plausible, which renders education status less influential in predicting conspiracy beliefs (Alper, 2021).…”
Section: Corruption and Conspiracy Beliefsmentioning
confidence: 98%
See 3 more Smart Citations
“…There is further evidence that conspiracy beliefs might be more reasonable in contexts with high risk of being under threat. In a recent study, it was found that the negative correlation between education and conspiracy beliefs is weaker in high corruption countries, as compared to low corruption ones (Alper, 2021). One potential explanation is that being suspicious of potential conspiracies is relatively more reasonable in high corruption contexts, and thus even highly educated people find them more plausible, which renders education status less influential in predicting conspiracy beliefs (Alper, 2021).…”
Section: Corruption and Conspiracy Beliefsmentioning
confidence: 98%
“…Each conspiracy theory, regardless of whether it is about evil scientists, shape-shifting aliens, or a secret society, functions as a "wake-up call" for people that are about to be harmed by an illintentioned outgroup, given that the theory is correct. Recent research suggested that certain social factors, including but not limited to corruption (Alper, 2021;Alper, Douglas et al, 2021) and inequality (Casara et al, 2022) could be triggering conspiracy beliefs since the perceived discrepancy in outcomescould be seen as signs of being exploited by outgroups. In this paper, we make use of a large, multisite dataset (23 countries, N > 20,000; Imhoff, Zimmer et al, 2022) to analyze how country-level corruption predicts conspiracy beliefs among people with right-wing and left-wing political orientations.…”
Section: Suspecting Foul Play When It Is Objectively There: the Assoc...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, lack of trust in media (Bruder & Kunert, 2021;Lockyer et al, 2021;Su et al, 2021), government and public health institutions (Bruder & Kunert, 2021;De Coninck et al, 2021;Kim & Kim, 2021;Pummerer et al, 2021), and science (Constantinou et al, 2020;Eberl et al, 2021;Erceg et al, 2020) have also been shown to play a key role in fostering conspiracy beliefs about the origins of COVID-19. A large-scale cross-country comparison showed that in countries where people find fewer reasons to trust institutions (e.g., countries that lack rule of law), there are significantly higher levels of COVID-19-related and general conspiracy beliefs (Alper, 2021).…”
Section: Conspiracy Beliefs and Generosity Across 52 Countries During The Covid-19 Pandemicmentioning
confidence: 99%